Revitalizing Textile Enterprises: A Holistic Approach to Value-Added Economical Production: Menghidupkan Kembali Perusahaan Tekstil: Pendekatan Holistik terhadap Produksi Ekonomis Bernilai Tambah - Yakhyаeva Inobat (Universitas Muhammadiyah Sidoarjo, 2023)
This study delves into the economic characteristics governing the value-added chain's formation within the framework of economical production in textile enterprises. The primary goal was to optimize material resource usage, increase product volume, boost profits, and enhance customer satisfaction through strategic reorganization and innovative technological implementation. Comparative analysis, statistical evaluation, logical thinking, and other scientific methodologies were employed to illustrate the correlation between the value-added chain and production costs in textile businesses. Findings suggest that economical production at these enterprises hinges on both organizational and methodological components, including forward tasks, employee quality, and the technology in use. The implications highlight that effective utilization of material resources, coupled with strategic changes in understanding cost-effective production, could lead to increased profitability and quality of goods. This approach serves as a progressive model for textile enterprises, offering promising potential for economic stabilization at a macro level.Highlights: Resource Optimization: Efficient use of raw materials in textile production. Strategic Reorganization: Importance of organizational elements in value-added, economical production. Macroeconomic Impact: The potential of enterprise efficiency for macroeconomic stabilization. Keywords: Textile Enterprises, Economical Production, Value-Added Chain, Resource Optimization, Profitability.